Search Based Software Engineering : 9th International Symposium, SSBSE 2017, Paderborn, Germany, September 9-11, 2017, Proceedings /: 9th International Symposium, SSBSE 2017, Paderborn, Germany, September 9-11, 2017, Proceedings. (2017) - Unknown
No abstract available